Investigation of thermal comfort and adaptation among the residents of cold climate in the lower Himalayan region of eastern India. Issue 6 (July 2022) - Thapa, Samar
Thermal comfort standards are required for overall indoor satisfaction and energy conservation. Even though the lower Himalayan region of Darjeeling has seen rapid growth in population due to its temperate type of climate, and thus resulting in manifold construction of concrete buildings, very few research on the built environment are reported from the region. In this paper, the author has discussed the yearlong thermal comfort study conducted in a naturally ventilated 3-storey un-insulated concrete building located at lower Himalayan region of Darjeeling, India. The mean indoor operative temperature were 16.7°C, 19.0°C and 22.3°C, the clothing insulation were 0.94 clo, 0.78 clo and 0.57 clo and the mean Griffiths' comfort temperature were 18.1°C, 19.6°C and 22.4°C during the cool, moderate and warm seasons, respectively. Seasonal and gender-wise differences are reported in the paper. A logistic regression is presented to show the variation of single and multiple layers of clothing used by subjects to adapt with the plummeting temperature. A modification in the comfort standards for the region with lower and upper limits as 16.2°C and 23.3°C is also proposed.